Joint Resposibility System As The Key Success Of Women's Cooperative Setia Bhakti Indonesian East Java Woman - Iwang Suwangsih; Fendy Suhariadi; Dwi Ratmawati; Sayyida Sayyida; Nuzulul Fatimah (International Journal Of Education, Social Studies, And Management (IJESSM), 2022)
The aim of this study is to describe about the key success of women's cooperative “Setia Bhakti Wanita (SBW) Jawa Timur” which used a joint responsibility system to manage the cooperative’s business so becomes a big cooperative in East Java Indonesia. It also becomes a learning place for the joint liability system for other cooperatives. This research is a descriptive qualitative research. The outcomes of this study found that the key to the success of the SBW women's cooperative in managing the cooperative business is consistently implementing a joint responsibility system, do monitoring and mentoring, using joint liability as an organizational culture, giving education and training to member, knowledge sharing between members.